2009
DOI: 10.1007/s00418-009-0650-9
|View full text |Cite
|
Sign up to set email alerts
|

Switching of actin isoforms in skeletal muscle differentiation using mouse ES cells

Abstract: Among six actin isoforms, alpha-skeletal and alpha-cardiac actins have similar amino acid components and are highly conserved. Although skeletal muscles essentially express alpha-skeletal actins in the adult tissue, alpha-cardiac isoform actin is prominent in the embryonic muscle tissue. Switching of actin isoforms from alpha-cardiac to alpha-skeletal actin occurs during skeletal muscle differentiation. The cardiac type alpha-actin is expressed in the regeneration and patho-physiological states of the skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A crucial step during early postnatal skeletal muscle development is the replacement of smooth muscle (α-SMA) and cardiac muscle (α-CAA) α-actin by skeletal muscle (α-SKA) α-actin (18, 19). This exchange requires the coordinated release of actin subunits, and cofilin2, a putative CAP2 interaction partner (9), has been implicated therein (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A crucial step during early postnatal skeletal muscle development is the replacement of smooth muscle (α-SMA) and cardiac muscle (α-CAA) α-actin by skeletal muscle (α-SKA) α-actin (18, 19). This exchange requires the coordinated release of actin subunits, and cofilin2, a putative CAP2 interaction partner (9), has been implicated therein (20).…”
Section: Resultsmentioning
confidence: 99%
“…S9 A , refs. 18 and 19). Specifically, α-SKA replaces α-SMA and α-CAA to become the major α-actin in differentiated myofibrils.…”
Section: Discussionmentioning
confidence: 98%
“…Electron microscopy analysis of mouse and human PSC-derived myofibers revealed that they exhibit highly organized sarcomeric units, reminiscent of the cytoarchitecture found in vivo (Hirsch et al, 1998;Skoglund et al, 2014). Myofibrils generated in these fibers can exhibit the appropriate organization of MyHC, troponin T, nebulin and titin, and undergo the stage-specific developmental transitions through α-actins (cardiac to skeletal) and MyHC (embryonic, fetal, and perinatal/fast) isoforms (Chal et al, 2015;Hirsch et al, 1998;Mizuno et al, 2009;Rohwedel et al, 1998b). Furthermore, desmin null mESCs have been used to demonstrate the important role of desmin in the early formation of myotubes (Höllrigl et al, 2002;Weitzer et al, 1995).…”
Section: Myofiber Maturation In Vitro Sarcomeres and Structural Assemblymentioning
confidence: 99%
“…By using cultivated mouse embryonic stem cells, this switching of actin isoforms was demonstrated by Mizuno et al (2009) for the Wrst time in vitro. Only after myotube formation, the cardiac type actin decreased and -skeletal actin increased and remained as the main actin component in mature skeletal muscle.…”
Section: Skeletal Musclementioning
confidence: 97%